2021
DOI: 10.4997/jrcpe.2021.306
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Long-Term Use of Four Common Conventional Disease Modifying Anti-Rheumatic Drugs in Rheumatoid Arthritis

Abstract: Conventional disease-modifying antirheumatic drugs (DMARDs) have been used in the management of rheumatoid arthritis for a long time. Whereas methotrexate (MTX) is the anchor drug, leflunomide, hydroxychloroquine and sulfasalazine are used along with MTX either in combination or sequentially. Together these four drugs are the most commonly used DMARDs. They are also used in combination with biological DMARDs (bDMARDs) to enhance their efficacy and MTX in particular to reduce antibodies against anti-tumour necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…9 Cost-effectiveness and efficacy/toxicity of MTX is very good. 10,21 MTX has been used for controlling disease activity and tapering steroid doses in many other rheumatic diseases, including juvenile idiopathic arthritis, systemic lupus erythematosus, Behçet's disease, vasculitis, seronegative spondyloarthritis, idiopathic inflammatory arthritis, and more. 10,21 However, surprisingly, there are few reports ESR and CRP.…”
Section: Ta B L E 2 Outcomes Of Treatment With Mtx In 59 Patients Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Cost-effectiveness and efficacy/toxicity of MTX is very good. 10,21 MTX has been used for controlling disease activity and tapering steroid doses in many other rheumatic diseases, including juvenile idiopathic arthritis, systemic lupus erythematosus, Behçet's disease, vasculitis, seronegative spondyloarthritis, idiopathic inflammatory arthritis, and more. 10,21 However, surprisingly, there are few reports ESR and CRP.…”
Section: Ta B L E 2 Outcomes Of Treatment With Mtx In 59 Patients Wit...mentioning
confidence: 99%
“…10,21 MTX has been used for controlling disease activity and tapering steroid doses in many other rheumatic diseases, including juvenile idiopathic arthritis, systemic lupus erythematosus, Behçet's disease, vasculitis, seronegative spondyloarthritis, idiopathic inflammatory arthritis, and more. 10,21 However, surprisingly, there are few reports ESR and CRP. 22 Thapa et al reported controlling arthritis attacks with MTX and prednisolone in a 53-year-old man with PR.…”
Section: Ta B L E 2 Outcomes Of Treatment With Mtx In 59 Patients Wit...mentioning
confidence: 99%
“…Biologics DMARDs (bDMARDs) are commonly used to treat patients with moderate-to-severe rheumatic disease who do not respond well to or cannot tolerate conventional synthetic DMARDs (12,13). However, none of these drugs or surgical treatments can completely cure autoimmune diseases, only relieve symptoms, they have side effects (severe gastrointestinal adverse reactions and immunosuppression leading to infection), and the price of biological agents is high (14)(15)(16). With the deepening of research, there is evidence that the intestinal microbiota can maintain the body's homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a lot of progress has been made in the development and utilization of disease control drugs for RA, especially biological targeted therapeutic drugs, this has significantly improved the clinical symptoms and disease activity of RA patients. [ 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a lot of progress has been made in the development and utilization of disease control drugs for RA, especially biological targeted therapeutic drugs, this has significantly improved the clinical symptoms and disease activity of RA patients. [5][6] Leflunomide (LEF) is one of the most commonly used disease-modifying anti-rheumatic drugs (DMARDs) for the treatment of RA in clinical practice, [7][8] and it was listed as one of the top three recommended treatments for rheumatoid arthritis by the American College of Rheumatology in 2008 [9]. Because its early use can significantly improve the prognosis of patients with RA, LEF has been effectively used for early RA and has been shown to significantly inhibit disease as assessed progression by joint imaging.…”
Section: Introductionmentioning
confidence: 99%